Maximizing the potential of captions for primary school ESL students' comprehension of English-language videos. Issue 7 (3rd September 2019) - Teng, Feng
Abstract: This study investigated the effects of captioned videos on ESL primary school students' comprehension of video content. A total of 182 primary school students watched two short English story videos in one of three conditions: fully captioned videos ( N = 62), keyword captioned videos ( N = 63), and uncaptioned videos ( N = 57). Each group included learners with higher and lower levels of English proficiency. Two videos were selected, and the second video was watched twice. After each video, all participants took a comprehension test, including global comprehension and detailed questions. Findings revealed that fully captioned group achieved the best results on the global comprehension questions. Significant differences between the fully captioned and keyword captioned videos on the detailed comprehension questions were not detected. Learners with a higher level of English proficiency and those who watched the video for a second time achieved better comprehension scores. These findings suggest that full captioning videos, rather than keyword captioning videos, should be considered when using video-based comprehension activities for ESL primary school learners. However, learners' English level and the frequency of video viewing should also be considered.